2022
DOI: 10.1186/s12916-022-02445-7
|View full text |Cite
|
Sign up to set email alerts
|

Practical guidance for planning resources required to support publicly-funded adaptive clinical trials

Abstract: Adaptive designs are a class of methods for improving efficiency and patient benefit of clinical trials. Although their use has increased in recent years, research suggests they are not used in many situations where they have potential to bring benefit. One barrier to their more widespread use is a lack of understanding about how the choice to use an adaptive design, rather than a traditional design, affects resources (staff and non-staff) required to set-up, conduct and report a trial. The Costing Adaptive Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Evidence from a hypothetical costing study suggested increased costs associated with the planning and setup of platform trials compared with traditional RCTs are due to the complex protocols and longer setup times . These increased costs were mitigated when more arms were added to the trial, which was less time intensive and reduced costs long term . Fourth, a comparison of platform trials with traditional parallel-arm RCTs was possible only on an indirect level.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from a hypothetical costing study suggested increased costs associated with the planning and setup of platform trials compared with traditional RCTs are due to the complex protocols and longer setup times . These increased costs were mitigated when more arms were added to the trial, which was less time intensive and reduced costs long term . Fourth, a comparison of platform trials with traditional parallel-arm RCTs was possible only on an indirect level.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive clinical trials may impact research and clinical workforce readiness. Adaptive trials require access to statistical, data and trial management staff who are fluent in their design 42 to manage the potential impact on trial costs. A mock-costing exercise completed with seven UK Clinical Trial Units estimated non-platform adaptive trials with pharmacologic interventions were 2-4% more expensive than a non-adaptive trial equivalent 43 .…”
Section: Introductionmentioning
confidence: 99%
“…The highest increase was for statistical staff, with lower increases for data and trial management staff 43 . Costings for appropriate statistical staff are highly dependent on the nature of the adaptive feature(s) included 42 . During trial conduct, adaptations that occur at prespecified interim analyses (e.g., sample size reestimation, multi-arm, multi-stage) may require more intensive ongoing input than adaptations that are managed on a day-to-day basis by software that implement methods to adaptively randomise individual participants (e.g., covariate-adjusted, response-adaptive).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations